Understanding the Metabolic Effects of Surgically Induced Renal Ischemia in Humans: A Temporal Approach - Bhargav Arimilli; Tyler A. On; Vaishnavi S. Srirama; Ye Yang; Gitanjali Asampille; Jeffrey R. Brender; Murali C. Krishna; Jessica Y. Hseuh; Viraj P. Chegu; Zachary Kozel; Sandeep Gurram; Mark W. Ball; et al. (Metabolites, 2025)
Background/Objectives: Thousands of nephrectomies are performed annually in the United States, but the short-term metabolic effects of surgically induced renal ischemia remain unclear. The conventional metabolic markers used to characterize post-surgical renal function, such as creatinine and GFR, are measured in the serum but do not provide metabolic information about the renal parenchyma itself. We aimed to characterize the immediate metabolic effects of surgical ischemia on renal parenchyma within a temporal framework. Methods: Timed renal parenchyma biopsies were collected from eight patients undergoing nephrectomy for renal cell carcinoma both prior to and after ligation of the renal hilum. These samples were ground, extracted, and analyzed using nuclear magnetic resonance (NMR) spectroscopy to measure changes in lactate, succinate, glucose, alanine, and glycine levels. Results: Due to experimental limitations, we were only able to draw limited conclusions from three patients. Of the five remaining patients, all had significant increases in lactate and succinate levels as a function of time, though the degree to which these increases occurred varied between each patient. Glucose levels generally decreased in the renal parenchyma but did not necessarily correlate with lactate production, assuming all glucose underwent fermentation to lactate in a hypoxic environment. Alanine and glycine levels did not change in a predictable pattern across patients. Conclusions: There are significant changes in lactate, glucose and succinate levels within minutes of the onset of renal ischemia in human patients. The degree of change in the metabolites analyzed varied significantly between patients. The length of surgical ischemia must be considered during surgical procurement of tumor specimens for metabolomic analysis.